2022
DOI: 10.1101/2022.12.06.518627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aβ-CT affective touch: Touch pleasantness ratings for gentle stroking and deep pressure exhibit dependence on A-fibers

Abstract: Gentle stroking of the skin is a common social touch behavior with positive affective consequences. A preference for slow versus fast stroking of hairy skin has been closely linked to the firing of unmyelinated C-tactile (CT) somatosensory afferents. Because the firing of CT afferents strongly correlates with touch pleasantness, the CT pathway has been considered a social-affective sensory pathway. Recently, ablation of the spinothalamic pathway- thought to convey all C-fiber sensations- in patients with cance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This indicates that plasticity in skin-to-brain circuits for affective touch produces a hedonic gradient ranging from appetitive to neutral to aversive. This is especially salient considering recent preclinical and clinical findings that have shown that pathways once thought of as dedicated labelled lines for "gentle touch" are not as strict in their coding 18,22 . Redundancies in pathways for a sensation as critical as pleasurable touch and plasticity in each neuron's ability to transmit broad modalities of cutaneous information is likely to be evolutionarily beneficial and indicates a high degree of combinatorial coding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that plasticity in skin-to-brain circuits for affective touch produces a hedonic gradient ranging from appetitive to neutral to aversive. This is especially salient considering recent preclinical and clinical findings that have shown that pathways once thought of as dedicated labelled lines for "gentle touch" are not as strict in their coding 18,22 . Redundancies in pathways for a sensation as critical as pleasurable touch and plasticity in each neuron's ability to transmit broad modalities of cutaneous information is likely to be evolutionarily beneficial and indicates a high degree of combinatorial coding.…”
Section: Discussionmentioning
confidence: 99%
“…10,16,17 Classic microneurography studies in humans had identified C-tactile afferents as key players in the transmission of pleasant slow stroking touch. 10,[18][19][20] A comparative class of low threshold C-fibers has also been identified in rodents. These afferents can be distinguished through their expression of a G-protein coupled receptor, MrgprB4.…”
Section: Introductionmentioning
confidence: 99%
“…CT receptors may also be only one of a putative family of receptors, each sensitive to distinct qualities of affiliative social touch 21,30 . There is also growing evidence that myelinated A fibers contribute to experienced pleasantness of soft stroking and pressure, 29,31,32 although the precise mechanisms by which this occurs—and whether it is a function of centrally modulated associative processes—is still not known 33 …”
Section: Characterizing Affiliative Touchmentioning
confidence: 99%